Analysis of Range Sidelobe of Pulse Doppler Fuze - Yuan Tao, Fan Mingjun (Hangkong bingqi, 2022)
When attacking cruise missile at ultra-low altitude, the pulse Doppler fuze may appear false alarm at the range sidelobe due to range ambiguity. In this paper, the ambiguity graph and the sea echo characteristics of the pulse Doppler fuze are analyzed, then three solutions of range sidelobe false alarm are proposed and compared, which are random pulsed phase modulation, random binary-phase modulation and repetitive frequency hopping. The results show that the repetitive frequency hopping method has good performance of anti range sidelobe.